Nursing Interventions in Cancer Pain Management: Enhancing Patient Outcomes through Integrated Pharmacological and Non-Pharmacological Approaches - Prabowo, Fajar; Setiawan, Dwi; Wijayanti, Hana (Java Nursing Journal, 2025)
Background: Cancer pain is one of the most challenging symptoms for patients, often leading to a significant decline in their quality of life. Despite advances in pain management, many cancer patients still experience insufficient pain relief. Nurses, who are on the front lines of patient care, play a vital role in managing this pain by using both pharmacological and non-pharmacological methods. However, the effectiveness of these combined interventions is not well understood. Purpose: The purpose of this study was to explore how nurses manage cancer pain and assess the impact of combining pharmacological and non-pharmacological treatments on pain levels and quality of life for cancer patients. Methods: This cross-sectional study was conducted at Columbia Asia Hospital Semarang over a 12-month period, from January 2024 to December 2024. We enrolled 420 participants—210 cancer patients and 210 registered nurses. Pain was assessed using the Numeric Rating Scale (NRS), and quality of life was measured using the Brief Pain Inventory (BPI). We used descriptive statistics, t-tests, and multivariate regression to analyze how different nursing interventions influenced patient outcomes. Results: Patients receiving a combination of pharmacological and non-pharmacological interventions reported significantly lower pain intensity (mean = 5.3, SD = 1.8) and better quality of life scores (mean = 68.4, SD = 12.3) than those who only received pharmacological treatments. Our regression analysis revealed that opioids were effective in reducing pain, while combining them with non-pharmacological interventions like cognitive-behavioral therapy improved patients' overall well-being. Conclusion: This study highlights the effectiveness of integrating pharmacological and non-pharmacological pain management strategies, improving both pain relief and quality of life for cancer patients. Nurses play a crucial role in these interventions, and further research should examine the long-term benefits and the potential use of digital tools in pain management.